2019
DOI: 10.1007/s00264-019-04341-x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction in association with medial unicompartmental knee replacement: a retrospective study comparing clinical and radiological outcomes of two different implant design

Abstract: Purpose Unicompartmental knee arthroplasty (UKA) combined with anterior cruciate ligament (ACL) reconstruction has recently been suggested as a feasible treatment option for young and active patients with medial compartment osteoarthritis (OA) and ACL deficiency. The aim of this study is to evaluate retrospectively the outcomes of two different implant designs in patients with medial OA secondary to traumatic ACL rupture, who underwent combined ACL reconstruction and unicompartmental knee replacement. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Li et al 20 reported a greater incidence of radiolucent lines at 2-years postoperatively in the FB group (37% vs. 8%; p = 0.02), while others demonstrated an increased incidence of radiolucent lines in the MB group (10.3% vs. 23.5%, p = 0.229; 69% vs. 24%, p = 0.001) 10,18 . Meanwhile, Andrea et al 22 revealed that no differences were found in RLLs between FM and MB group. Based on the cumulative data, no significant difference was found in the frequency of RLLs between the FB and MB groups (42.0% vs. 19.0%, OR = 0.56; 95% CI 0.10-3.05; p = 0.51).…”
Section: Radiological Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…Li et al 20 reported a greater incidence of radiolucent lines at 2-years postoperatively in the FB group (37% vs. 8%; p = 0.02), while others demonstrated an increased incidence of radiolucent lines in the MB group (10.3% vs. 23.5%, p = 0.229; 69% vs. 24%, p = 0.001) 10,18 . Meanwhile, Andrea et al 22 revealed that no differences were found in RLLs between FM and MB group. Based on the cumulative data, no significant difference was found in the frequency of RLLs between the FB and MB groups (42.0% vs. 19.0%, OR = 0.56; 95% CI 0.10-3.05; p = 0.51).…”
Section: Radiological Outcomesmentioning
confidence: 97%
“…Clinical outcomes. Nine studies assessed the Knee Society Score (KSS) 1,[9][10][11][12]15,19,20,22 ; six studies assessed the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score 11,[16][17][18]20,22 ; three studies assessed the Oxford Knee Score (OKS) 5,15,17 ; one study assessed the Italian Orthopedic UKR's Users Group (GIUM) score 9 ; one study assessed the Bristol knee score 5 ; and one study assessed the International Knee Society score 8 . No significant statistical differences were reported between the FB and MB groups on all knee scores measured in these studies.…”
mentioning
confidence: 99%
“…All were published between 2006 and 2019. The search resulted in one comparative case series (Level III) [19], four prospective cohort studies (Level III) [9,12,16,18] and four case series (Level IV) [11,13,17,20]. Average follow-up periods ranged from 2 years to 7.8 years in a longterm study.…”
Section: Search Resultsmentioning
confidence: 99%
“…OA was diagnosed pre-operatively using long-leg standing and standard radiographs; in four studies [12,13,18,19] valgus stress radiographs in 20° of flexion were performed. Only in two studies magnetic resonance imaging (MRI) was performed to evaluate the knee joint preoperatively [17,19].…”
Section: Radiological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation